The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/genes12010069
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Signaling Molecules Positively Regulate c-di-GMP Effector PelD Encoding Gene and PEL Exopolysaccharide Biosynthesis in Extremophile Bacterium Acidithiobacillus thiooxidans

Abstract: Acidithiobacillus species are fundamental players in biofilm formation by acidophile bioleaching communities. It has been previously reported that Acidithiobacillus ferrooxidans possesses a functional quorum sensing mediated by acyl-homoserine lactones (AHL), involved in biofilm formation, and AHLs naturally produced by Acidithiobacillus species also induce biofilm formation in Acidithiobacillus thiooxidans. A c-di-GMP pathway has been characterized in Acidithiobacillus species but it has been pointed out that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The construction of an At. thioooxidans Δ pelD null-mutant strain revealed that PEL exopolysaccharide is involved in its biofilm architecture since their biofilms were more sensitive to mechanical stress and easily removable from sulfur upon mechanical stress in comparison to wild-type strains (Díaz et al 2020 ). The analysis of L. ferriphilium DSM 14647 T complete genome sequence showed that cellulose, PEL, and poly-1,6- N -acetyl-D-glucosamine (PGA) can be synthesized by this strain.…”
Section: Biofilm Formation and Molecular Controlsmentioning
confidence: 99%
See 2 more Smart Citations
“…The construction of an At. thioooxidans Δ pelD null-mutant strain revealed that PEL exopolysaccharide is involved in its biofilm architecture since their biofilms were more sensitive to mechanical stress and easily removable from sulfur upon mechanical stress in comparison to wild-type strains (Díaz et al 2020 ). The analysis of L. ferriphilium DSM 14647 T complete genome sequence showed that cellulose, PEL, and poly-1,6- N -acetyl-D-glucosamine (PGA) can be synthesized by this strain.…”
Section: Biofilm Formation and Molecular Controlsmentioning
confidence: 99%
“…ferrooxidans T (Gonzalez et al 2013 ), while the addition of middle chain AHLs resulted in an enhanced biofilm formation of At. thiooxidans on sulfur surfaces (Díaz et al 2020 ). At least 75 genes have been predicted to be modulated by QS in At.…”
Section: Biofilm Formation and Molecular Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, derepressed Clp alters the expression level of abundant genes, such as those coding virulence factors ( 58 ). There is reason to expect that the DSF integrated with c-di-GMP pathways plays pivotal roles in population communication and adaptation, just like the connection between AHL-mediated QS and c-di-GMP during the process of colonization and dissolution of minerals ( 4 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…This locus consists of two convergent genes for the leptospiral lttR and lttI , and a third ORF has been found in the lttIR intergenic region [ 45 ]. A SdiA-like protein has been identified in Acidithiobacillus thiooxidans as strongly likely to take part in QS transcriptional regulation [ 44 ]. SdiA is an orphan QS transcriptional regulator, independent of the AHL synthase.…”
Section: Qs and Second Messenger In Acidophilesmentioning
confidence: 99%